OPTIMALISASI MANAJEMEN HIPERTENSI PADA LANSIA DI WILAYAH PESISIR KAMPUNG MELAYU, AMPENAN NTB - Rozikin, Rozikin; Adyana, Angga; Setyaningrum, Tri Wahyu; Widyaswara, Gravinda; Hapsari, Widie Kemala; Hayatillah, Raudhah (Jurnal Abdi Insani, 2025)
High blood pressure, also known as hypertension, is a medical condition that affects blood pressure and can lead to complications such as stroke and heart disease. Hypertension is suffered by many people living in coastal areas due to an unhealthy lifestyle and consuming salty fish. To reduce the number of people with hypertension in coastal areas, community service activities related to hypertension management were carried out. The methods used in the community service were problem identification with the Delbecq (non-scoring method) method, data collection through interviews with questionnaires and observations of 70 participants, problem intervention through poster counseling and tension checks, data analysis using univariate analysis. The results of the community service were dominated by 55 women (79%) and middle-aged (45-59 years) 46 people (66%). The results of the questionnaire search showed that as many as 60 people (86%) respondents had heavy physical activity, 39 people (56%) respondents had a good level of knowledge and hypertension management, 42 people (60%) were known to often consume salted fish and 48 people (69%) were found to have hypertension. The high rate of hypertension sufferers in the coastal area of Kampung Melayu is due to the lack of counseling that focuses on dietary management and increasing public awareness about the risk of hypertension related to the consumption of high-sodium foods.